Clinicopathological Bird's-Eye View of Left Atrial Myocardial Fibrosis in 121 Patients With Persistent Atrial Fibrillation: Developing Architecture and Main Cellular Players. (July 2020) - Callegari, Sergio; Macchi, Emilio; Monaco, Rodolfo; Magnani, Luca; Tafuni, Alessandro; Croci, Stefania; Nicastro, Maria; Garrapa, Valentina; Banchini, Antonio; Becchi, Gabriella; Corradini, Emilia; Goldoni, Matteo; et al.
Abstract : Background: Scientific research on atrial fibrosis in atrial fibrillation (AF) has mainly focused on quantitative or molecular features. The purpose of this study was to perform a clinicoarchitectural/structural investigation of fibrosis to provide one key to understanding the electrophysiological/clinical aspects of AF. Methods: We characterized the fibrosis (amount, architecture, cellular components, and ultrastructure) in left atrial biopsies from 121 patients with persistent/long-lasting persistent AF (group 1; 59 males; 60±11 years; 91 mitral disease–related AF, 30 nonmitral disease–related AF) and from 39 patients in sinus rhythm with mitral valve regurgitation (group 2; 32 males; 59±12 years). Ten autopsy hearts served as controls. Results: Qualitatively, the fibrosis exhibited the same characteristics in all cases and displayed particular architectural scenarios (which we arbitrarily subdivided into 4 stages) ranging from isolated foci to confluent sclerotic areas. The percentage of fibrosis was larger and at a more advanced stage in group 1 versus group 2 and, within group 1, in patients with rheumatic disease versus nonrheumatic cases. In patients with AF with mitral disease and no rheumatic disease, the percentage of fibrosis and the fibrosis stages correlated with both left atrial volume index and AF duration. The fibrotic areas mainly consisted of type I collagen with only a minor cellular component (especially fibroblasts/myofibroblasts; average value range 69–150 cells/mm 2, depending on the areas in AF biopsies). A few fibrocytes—circulating and bone marrow-derived mesenchymal cells—were also detectable. The fibrosis-entrapped cardiomyocytes showed sarcolemmal damage and connexin 43 redistribution/internalization. Conclusions: Atrial fibrosis is an evolving and inhomogeneous histological/architectural change that progresses through different stages ranging from isolated foci to confluent sclerotic zones which—seemingly—constrain impulse conduction across restricted regions of electrotonically coupled cardiomyocytes. The fibrotic areas mainly consist of type I collagen extracellular matrix and, only to a lesser extent, mesenchymal cells. Abstract : Supplemental Digital Content is available in the text.